2016
DOI: 10.1007/s00432-016-2299-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for intestinal metaplasia in a southeastern Chinese population: an analysis of 28,745 cases

Abstract: This study confirms age, male gender, gastric ulcer, bile reflux, H. pylori infection, severe degree of chronic and acute inflammation to be the risk factors for intestinal metaplasia. We speculate that the gross domestic product per capita of different areas may be a potential independent risk factor impacting the incidence of intestinal metaplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
2
22
0
3
Order By: Relevance
“…The present results indicated that H. pylori infection was positively associated with IM. This is consistent with results from earlier studies, which examined the prevalence of the infection in IM in large cohorts (21,22). Based on this information, H. pylori infection was indicated to be inversely associated with HPs.…”
Section: Discussionsupporting
confidence: 91%
“…The present results indicated that H. pylori infection was positively associated with IM. This is consistent with results from earlier studies, which examined the prevalence of the infection in IM in large cohorts (21,22). Based on this information, H. pylori infection was indicated to be inversely associated with HPs.…”
Section: Discussionsupporting
confidence: 91%
“…IM places patients at a higher risk of developing gastric adenocarcinoma than patients without IM (34). In addition, mounting epidemiological evidence has demonstrated that exposure to bile acids can induce IM in the stomach (19). Tatsugami et al reported that grades of atrophy and IM are significantly positively correlated with bile acid concentrations in patients with Helicobacter pylori infections (18).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental studies have reported that AG and IM are associated with the phenomenon of duodenogastric reflux (DGR) (16,17). Bile acids, which are the primary duodenal components of DGR, are generally considered to be carcinogens in gastric IM formation and gastric tumourigenesis (18,19). Bile acids, particularly CDCA and DCA, have been reported to be associated with the induction of CDX2 and MUC2 expression.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that chronic environmental stimulation leads to gastric IM, such as Helicobacter pylori (Hp) infection and bile acids (BA) re ux [4,5]. However, whether Hp eradication could prevent the occurrence or further development of gastric cancer is still controversial [6,7], indicating other factors may contribute to the development of IM.…”
Section: Introductionmentioning
confidence: 99%